2017
DOI: 10.1155/2017/9312329
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Synovial Mesenchymal Stem Cell Derived from Hip Joints: A Comparative Analysis with a Matched Control Knee Group

Abstract: Purpose. To determine the characteristics of MSCs from hip and compare them to MSCs from knee. Methods. Synovial tissues were obtained from both the knee and the hip joints in 8 patients who underwent both hip and knee arthroscopies on the same day. MSCs were isolated from the knee and hip synovial samples. The capacities of MSCs were compared between both groups. Results. The number of cells per unit weight at passage 0 of synovium from the knee was significantly higher than that from the hip (P < 0.05). Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 30 publications
(41 reference statements)
5
83
0
Order By: Relevance
“…Hagmann et al reported differences between donor‐typed bone marrow and synovial MSCs with the latter uniformly exhibiting trilineage differentiation and strongly positive for CD73, CD90, CD105, and MHC‐I although small levels of CD34 and CD45 positive cells were also detected. A comparable yield of cells from synovium have been isolated from pathological knee and hip joints exhibiting a “mixed” cell‐surface marker profile similar to this study . Furthermore, a similar cell‐surface marker expression profile for synovium‐derived trilineage positive cells has been reported in this study, though the authors have interpreted CD166 as a possible discriminating factor between multipotent and fibroblastic cells .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Hagmann et al reported differences between donor‐typed bone marrow and synovial MSCs with the latter uniformly exhibiting trilineage differentiation and strongly positive for CD73, CD90, CD105, and MHC‐I although small levels of CD34 and CD45 positive cells were also detected. A comparable yield of cells from synovium have been isolated from pathological knee and hip joints exhibiting a “mixed” cell‐surface marker profile similar to this study . Furthermore, a similar cell‐surface marker expression profile for synovium‐derived trilineage positive cells has been reported in this study, though the authors have interpreted CD166 as a possible discriminating factor between multipotent and fibroblastic cells .…”
Section: Discussionsupporting
confidence: 82%
“…A comparable yield of cells from synovium have been isolated from pathological knee and hip joints exhibiting a "mixed" cell-surface marker profile similar to this study. 22 Furthermore, a similar cell-surface marker expression profile for synovium-derived trilineage positive cells has been reported in this study, though the authors have JOURNAL OF ORTHOPAEDIC RESEARCH ® JANUARY 2020 interpreted CD166 as a possible discriminating factor between multipotent and fibroblastic cells. 26 In contrast, assessing the ameliorative effects of synovial MSCs in an osteoarthritic mouse model, synovial MSCs were reported to be highly positive for CD73, CD90, and CD105.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Whether this was due to an effect of QDs or to drift of MSC immunophenotype over the passages in separate cultures is not clear, and further studies are needed in this area. Although molecular markers continue to be used to characterize stem cell populations, recent studies with human MSCs indicate that cells isolated from different donors (Szepesi et al, ) or from different sites from the same donor (Hatakeyama et al, ; Sacchetti et al, ) and cells treated with different enzymatic digestion methods for detachment (Tsuji et al, ) can have different surface antigen expression and even MSCs with identical cell surface phenotype from different tissues and donors have distinct transcriptomic signatures and differentiation capacities, likely due to the broad overlap of cells with MSC markers with other cell populations (Assoni, Coatti, Valadares, et al, ; Sacchetti et al, ). Thus, the immunophenotypic characterization of MSCs remains unclear, and MSCs are currently best defined functionally.…”
Section: Discussionmentioning
confidence: 99%